2015
DOI: 10.1007/jhep07(2015)044
|View full text |Cite
|
Sign up to set email alerts
|

Further holographic investigations of big bang singularities

Abstract: Abstract:We further explore the quantum dynamics near past cosmological singularities in anisotropic Kasner-AdS solutions using gauge/gravity duality. The dual description of the bulk evolution involves N = 4 super Yang-Mills on the contracting branch of an anisotropic de Sitter space and is well defined. We compute two-point correlators of YangMills operators of large dimensions using spacelike geodesics anchored on the boundary. The correlator between two points separated in a direction with negative Kasner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 33 publications
3
73
0
Order By: Relevance
“…To probe these fascinating phenomena in field theory, one should employ some non-local observables such as equal time two point correlation function for a scalar operator, Wilson loop, and holographic entanglement entropy, which are dual to the geodesic length, minimal area, and minimal volume individually in the saddle point approximation. It has been shown that these observables can probe the nonequilibrium thermalization behavior [4][5][6][7][8][9][10][11][12][13][14][15], superconducting phase transition [16][17][18][19][20][21][22][23], and cosmological singularity [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…To probe these fascinating phenomena in field theory, one should employ some non-local observables such as equal time two point correlation function for a scalar operator, Wilson loop, and holographic entanglement entropy, which are dual to the geodesic length, minimal area, and minimal volume individually in the saddle point approximation. It has been shown that these observables can probe the nonequilibrium thermalization behavior [4][5][6][7][8][9][10][11][12][13][14][15], superconducting phase transition [16][17][18][19][20][21][22][23], and cosmological singularity [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate the behaviour of correlators near the singularity we follow the prescriptions of [10,12]. For the sake of brevity we fix the boundary at the radial slice r = r 0 = 1, and the turning point of the probe geodesic in the bulk at r = r * where we assume r * → 0.…”
Section: P > 0 Casementioning
confidence: 99%
“…We pursue the approach undertaken in [10,11,12]. Using the geodesic approximations we compute the two-point correlators for largely massive operators.…”
Section: Introductionmentioning
confidence: 99%
“…Several important advances in this direction have been made, within the general framework of strings and holography, e.g. [3][4][5], and through the embedding of cosmological crunching geometries in Anti-de Sitter (AdS) spacetime [6][7][8][9], and more recently in [10,11]. The main goal in a holographic setting of this type is to find out how a given bulk (cosmological) singularity makes itself known within the dual quantum field theory.…”
Section: Introductionmentioning
confidence: 99%
“…The implication of the behaviour of such probe geodesics for frequency space (thermal) Wightman functions was worked out precisely in [13] applying a WKB approximation to wave equations in the bulk. The general idea of probing bulk singularities with correlators in the geodesic limit has proved to be extremely attractive and has been applied recently to deduce a direct signature of singularities in anisotropic Kasner-AdS solutions within the holographic setting [10,11,14].…”
Section: Introductionmentioning
confidence: 99%